Fuel‐lean VOCs combustion in a porous burner stacked with alumina balls: A case for ethylene combustion. (21st December 2018) - Ling, Bo; Ling, Zhongqian; Kuang, Min; Zeng, Xianyang; Li, Xiaojin; Xu, Yang; Chen, Yangxi
Summary: A porous burner stacked in turn with 3‐ and 9‐mm alumina pellets was established to perform C2 H4 combustion experiments by acquiring the flammable limits, temperature variation characteristics, combustion wave velocity, pollutant emissions, and treatment efficiency. The burner operated well at equivalence ratios within 0.3 to 0.7. Larger alumina pellets widened the burner's lower flammable limit. As the flame propagated downstream, the higher premixed gas flow velocity and larger alumina pellets, the higher combustion wave velocity, whereas the circumstances were opposite as the flame spread upstream. The combustion temperature increased with the equivalence ratio and premixed gas flow velocity. In response to the effect of the alumina pellet dimension, 3‐mm alumina pellets corresponded to higher combustion temperatures, lower CO emissions, and higher treatment efficiency than those less than 9‐mm conditions. Abstract : Schematic representation of flame behaviors in the porous burner with different alumina pellets.